Knowledge about Alzheimer’s disease in medical, nursing, and psychology students in Ecuador: A problem that needs an urgent solution - José Alejandro Valdevila Figueira; María Alejandra Espinoza de los Monteros Andrade; Xavier Rodrigo Yambay-Bautista; Andrés Ramírez; Indira Dayana Carvajal Parra; Rocío Valdevila Santiesteban; María José Pico; Jose A. Rodas (PLoS ONE, 2026)
Background Alzheimer’s disease represents one of the greatest healthcare challenges of the 21st century due to the aging population and its impact on the quality of life of patients and their families. Preparing future healthcare professionals to address this condition is crucial. Aims This article analyzes the level of knowledge about Alzheimer’s disease held by university students in medicine, nursing, and psychology, highlighting the differences and similarities between disciplines and proposing strategies to improve training in this field. Methods A cross-sectional study was conducted with a convenience sample of 1,023 Ecuadorian students: nursing (n = 727, 71.1%), medicine (n = 170, 16.6%), and psychology (n = 126, 12.3%). Participants completed the Alzheimer’s Disease Knowledge Scale (ADKS) and a demographic survey. The percentage of correct answers on the ADKS was used to assess knowledge levels. Results The overall percentage of correct answers was 54.68%, indicating a limited level of knowledge. Medical students obtained the highest mean score (17.44 [SD: 2.864]), followed by psychology (16.28 [SD: 2.348]) and nursing (16.18 [SD: 2.649]). A weak but significant correlation was found between knowledge level and prior contact with people with dementia (P < 0.001). Conclusions Students across all disciplines demonstrated a broad knowledge gap regarding Alzheimer’s disease, although medical students obtained slightly higher scores than psychology and nursing students. The findings highlight the need for improved educational training and curriculum development to enhance dementia knowledge, especially in psychology and nursing programs.